1972
DOI: 10.1002/bjs.1800590702
|View full text |Cite
|
Sign up to set email alerts
|

Malignant tumours of the bile-ducts

Abstract: SUMMARYThe 77 cases of malignant neoplasm of the extrahepatic bile-ducts treated at the Lahey Clinic between 1965 and 1969 are reviewed. Exploratory laparotomy was performed in 68 cases, although in 9 cases operation was not indicated because of the patients' poor condition. Of the 68 surgical patients, 24 (35 per cent) had a radical procedure, of which 17 survived for more than I year and 5 are still alive more than 3 years later, 3 having no evidence of recurrent disease. Forty-one patients had palliative tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

1973
1973
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…The ideal surgical treatment-excision of the neoplasm-is rarely feasible (30). Moreover, with lesions high in the porta hepatis, there is rarely sufficient ductal tissue proximal to the neoplasm to permit conventional bypass ( 15,16,(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal surgical treatment-excision of the neoplasm-is rarely feasible (30). Moreover, with lesions high in the porta hepatis, there is rarely sufficient ductal tissue proximal to the neoplasm to permit conventional bypass ( 15,16,(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Like central lesions, the more common (60%) peripheral bile duct cancers are demonstrated in direct cholangiography as nonspecific stenoses or obstructions (Longmire et al, 1973;Ohto et al, 1980;Tompkins et al, 1981;Warren et al, 1972). They may also present with bilevel obstruction as a result of central lymphadenopathy.…”
Section: Stricturesmentioning
confidence: 99%
“…Warren, Mountain & Lloyd-Jones (1972), from the Lahey Clinic, have reviewed seventy-seven cases of malignant tumour of the bile ducts and found that radical surgery was possible in twenty-four of these, in which seventeen survived for more than a year, and five are still alive over 3 years later. Surgery comprised either pancreaticoduodenectomy, or resection with -end-to-end anastomosis.…”
Section: Liver and Biliary Systemmentioning
confidence: 99%